Model for warehouse shipping and store provisioning: Worten case study - Marques, Miguel Martins Soares (2021)
Nowadays with the increase of competition and demanding customers, it is normal for companies to feel the need of improving their internal processes, using them to gain a margin over competition and reaching the customer faster. Worten, is the best electronic retail company in Portugal, but to increase its value, can recognize that should be in continuous improvement on its supply chain and on internal processes that are ruling for too long, becoming obsolete and not adding value for the final customer. The capability of Worten to always identifying improvement opportunities and wanting to do better, culminated in the realization of this project. In this project, the actual processes in practice in Worten warehouse were described and afterwards th were analysed and improving proposals were presented as well as the impact before and after their implementation.